Clinical Characteristics of Disability in Patients with Indoor Air-Related Environmental Intolerance - Aki Vuokko; Kirsi Karvala; Hille Suojalehto; Harri Lindholm; Sanna Selinheimo; Marja Heinonen-Guzejev; Sami Leppämäki; Sebastian Cederström; Christer Hublin; Katinka Tuisku; Markku Sainio (Elsevier, 2019)
Background: Chronic nonspecific symptoms attributed to indoor nonindustrial work environments are common and may cause disability, but the medical nature of this disability is unclear. The aim was to medically characterize the disability manifested by chronic, recurrent symptoms and restrictions to work participation attributed to low-level indoor pollutants at workplace and whether the condition shares features with idiopathic environmental intolerance. Methods: We investigated 12 patients with indoor air-related work disability. The examinations included somatic, psychological, and psychiatric evaluations as well as investigations of the autonomic nervous system, cortisol measurements, lung function, and allergy tests. We evaluated well-being, health, disability, insomnia, pain, anxiety, depression, and burnout via questionnaires. Results: The mean symptom history was 10.5 years; for disabling symptoms, 2.7 years. Eleven patients reported reactions triggered mainly by indoor molds, one by fragrances only. Ten reported sensitivity to odorous chemicals, and three, electric devices. Nearly all had co-occurrent somatic and psychiatric diagnoses and signs of pain, insomnia, burnout, and/or elevated sympathetic responses. Avoiding certain environments had led to restrictions in several life areas. On self-assessment scales, disability showed higher severity and anxiety showed lower severity than in physician assessments. Conclusion: No medical cause was found to explain the disability. Findings support that the condition is a form of idiopathic environmental intolerance and belongs to functional somatic syndromes. Instead of endless avoidance, rehabilitation approaches of functional somatic syndromes are applicable. Keywords: Building-related intolerance, Disability evaluation, Environmental intolerance, Functional somatic syndromes, Indoor air